2022
DOI: 10.1021/acs.jafc.2c01731
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids as Functional Food Components: Benefits in Skin Improvement and Disease Prevention

Abstract: Sphingolipids are ubiquitous components in eukaryotic organisms and have attracted attention as physiologically functional lipids. Sphingolipids with diverse structures are present in foodstuffs as these structures depend on the biological species they are derived from, such as mammals, plants, and fungi. The physiological functions of dietary sphingolipids, especially those that improve skin barrier function, have recently been noted. In addition, the roles of dietary sphingolipids in the prevention of diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 134 publications
0
10
0
Order By: Relevance
“…Sphingolipids are a class of lipids existing in all living organisms as the important structural components of membranes. Plenty of research shows that sphingolipids play key roles in regulating the growth, differentiation, migration, and apoptosis of cells and the immune system in many mammalian cells [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Ceramides are a group of sphingolipids composed of sphingosine and a fatty acid via an amide linkage.…”
Section: Introductionmentioning
confidence: 99%
“…Sphingolipids are a class of lipids existing in all living organisms as the important structural components of membranes. Plenty of research shows that sphingolipids play key roles in regulating the growth, differentiation, migration, and apoptosis of cells and the immune system in many mammalian cells [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Ceramides are a group of sphingolipids composed of sphingosine and a fatty acid via an amide linkage.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al found that the higher the degree of saturation of phospholipids, the greater the protective effect of curcumin against light degradation. Some studies , also demonstrated that SM had the potential in protecting human skin against UV photodamage. So, it is speculated that SM could protect lutein from photochemical oxidation induced by UV irradiation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Taken together, these data raise the possibility that differences in lipid metabolism may underlie the choice between a vegetarian and non-vegetarian diet. Lipid profiles of foods from animal sources are significantly different from those of plant sources, particularly with regard to complex lipids such as sphingolipids; and recent studies have brought attention to the importance of dietary sphingolipids in health [94][95][96][97]. In this regard it is of interest to note that complex lipids, particularly sphingolipids, play critical roles in nervous system development and function [98,99], and that most of the vegetarianism-associated genes identified in this study have also been linked to psychological and neurological traits and diseases including Niemann-Pick disease, Alzheimer's disease, epilepsy, anxiety, depression, alcoholism, schizophrenia, autism spectrum disorder, cognitive performance and others (see S2 and S8 Tables).…”
Section: Plos Onementioning
confidence: 99%